Chronic Obstructive Pulmonary Disease and the Risk of Esophagitis, Barrett's Esophagus, and Esophageal Adenocarcinoma: A Primary Care Case-Control Study - Menon, Shyam; Nightingale, Peter; Trudgill, Nigel (Journal of clinical gastroenterology, 2019)
Chronic gastroesophageal reflux predisposes to the development of esophageal adenocarcinoma (EAC). Asthma and medication to treat it are associated with gastroesophageal reflux and EAC. We studied subjects with chronic obstructive pulmonary disease (COPD) to examine the relationship between COPD and medication used to treat it, and the risk of reflux esophagitis, Barrett's esophagus, and EAC. A case-control study from the UK General Practice Research Database was conducted. Cases were aged 50 or above with a diagnosis of COPD and were matched with controls without a diagnosis of COPD by age, general practitioners practice, and time on the database. EAC was confirmed by cross-referencing cancer registry data. Cox-regression analysis was performed to assess the relationship between COPD, reflux esophagitis, Barrett's esophagus, and EAC. A total of 45,141 cases were studied [24,464 male, age 75 (50 to 100) years]. Among COPD cases there were 55 esophageal cancers (30 EAC) and 506 Barrett's esophagus, compared with 62 (34 EAC) and 329 Barrett's esophagus among controls. COPD was not associated with EAC on univariable [0.92 (0.56 to 1.50), P=0.73] and multivariable analysis [0.85 (0.52 to 1.40), P=0.53]. COPD was however, associated with Barrett's esophagus on univariable [0.92 (0.56 to 1.50), P=0.73] and multivariable [1.53 (1.31 to 1.78), P<0.001] analysis and reflux esophagitis on univariable [1.41 (1.36 to 1.48), P<0.001] and multivariable [1.33 (1.27 to 1.40), P<0.001] analysis. COPD is associated with an increased risk of reflux esophagitis and Barrett's esophagus but not EAC.